Diagnostyka zapalenia zatok obocznych nosa w kontekście badań obrazowych = Sinusitis in the context of diagnostics imaging - Gustaw Wójcik; Anna Szulc; Teresa Stawińska (Kazimierz Wielki University, 2017)
Wójcik Gustaw, Szulc Anna, Stawińska Teresa. Diagnostyka zapalenia zatok obocznych nosa w kontekście badań obrazowych = Sinusitis in the context of diagnostics imaging. Journal of Education, Health and Sport. 2016;6(11):63-72. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163932 http://ojs.ukw.edu.pl/index.php/johs/article/view/3963       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016.       DIAGNOSTYKA ZAPALENIA ZATOK OBOCZNYCH NOSA W KONTEKŚCIE BADAŃ OBRAZOWYCH SINUSITIS IN THE CONTEXT OF DIAGNOSTICS IMAGING   Wójcik Gustaw1, 2, Szulc Anna3, Stawińska Teresa3   1 Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, Wydział Nauk o Zdrowiu i Nauk Społecznych 2 Uniwersytet Medyczny w Lublinie, Katedra Rehabilitacji, Fizjoterapii i Balneoterapii, Zakład Balneoterapii 3 Uniwersytet Medyczny w Lublinie, Katedra Rehabilitacji, Fizjoterapii i Balneoterapii, Zakład Rehabilitacji       dr n. med. Wójcik Gustaw1,2 dr n. o zdr. Szulc Anna3 dr n. o zdr. Stawińska Teresa3   Słowa kluczowe: zatoki przynosowe, zapalenie zatok, kompleksy ujściowo-przewodowe, diagnostyka obrazowa   STRESZCZENIE             Zapalenie zatok przynosowych jest dość częstym schorzeniem zaliczanym do chorób górnych dróg oddechowych. Podłożem zapalenia zatok mogą być wirusy, bakterie a nawet grzyby. Prawidłowa diagnostyka umożliwia podjęcie skutecznego leczenia. Klasyczne zdjęcie rtg jest badaniem obrazowym tanim i popularnym, do którego pacjenci mają łatwy dostęp, lecz jego użyteczność ma spore ograniczenia. Złotym standardem w postępowaniu diagnostyczno-terapeutycznym pozostaje TK, jednak i ona nie jest metodą idealną. Uzupełnieniem jej jest tomografia MRI dzięki, której można łatwiej zróżnicować tkanki miękkie. Nie można jednak podejmować leczenia zapalenia zatok wyłącznie na podstawie objawów radiologicznych, gdyż konieczne do podjęcia terapii jest ich współwystępowanie z objawami klinicznymi.   Key words: paranasal sinuses, sinusitis, ostiomeatal complex, diagnostic imaging   SUMMARY Rhinosinusitis is a frequent common chronic disease that is included to upper airways diseases. The disease can be caused by viruses, bacteria and even fungi. The effective treatment depends on proper diagnostics. The classic radiogram is an cheap and popular examination. Patients have easy access to it but its usefulness is limited. CT (Computed Tomography) is the gold standard of diagnostic and therapeutic management but this is not perfect method. MRI (Magnetic Resonance Imaging) is the complement and can make easier to differentiate the soft tissues. However, the treatment should not be started only on the basis of radiological symptoms, because there is need to occur also clinical symptoms.